2021
DOI: 10.1007/s12667-021-00451-x
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of effective solar cells

Abstract: We propose a two-stage multi-objective optimization framework for full scheme solar cell structure design and characterization, cost minimization and quantum efficiency maximization. We evaluated structures of 15 different cell designs simulated by varying material types and photodiode doping strategies. At first, non-dominated sorting genetic algorithm II (NSGA-II) produced Pareto-optimal-solutions sets for respective cell designs. Then, on investigating quantum efficiencies of all cell designs produced by NS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…In addition, the authors concluded that through a solar cell design, as well as a comparison and optimization of the doped zinc oxide layer (which is based on the transparent conductive oxide (TCO) layer and rough silver back reflector (BR)), internal quantum efficiency can be optimized. This proposed study reported a total internal quantum efficiency of 60.31% [26].…”
Section: Introductionmentioning
confidence: 78%
“…In addition, the authors concluded that through a solar cell design, as well as a comparison and optimization of the doped zinc oxide layer (which is based on the transparent conductive oxide (TCO) layer and rough silver back reflector (BR)), internal quantum efficiency can be optimized. This proposed study reported a total internal quantum efficiency of 60.31% [26].…”
Section: Introductionmentioning
confidence: 78%